Intellectual Property And Ownership - Mohnani, Aryan (Trinity Law Review, 2021)
The world is continuously being technologically advanced, whether it is in medicine or business. Humans have been utilizing and making the most value of their ideas and thoughts. As we live in this dynamically fast-paced world, we need to ensure that the products of human intellect aren’t being pinched and stolen away. This is when Intellectual Property comes to mind. These can be protected by the law so that the valuable thoughts and ideas of the individual are nourished and awarded, either by financial or general recognition. Huge companies like Microsoft to Sony, all make sure that their designs and inventions are protected and they do that by registering them as Intellectual Properties. That’s why it is crucial to learn more about Intellectual Property and its rights.